Contributing factors for successful implementation of erosion and sediment control plan in Malaysia - Asri Syahmi, Asnor (2019)
The mixing of water and soil can give a significant impact to the environment. Therefore, Erosion and Sediment Control Plan (ESCP) is necessary to reduce the adverse effects of sediment transport from on-site to off-site areas. This study aims to investigate the factors for implementing ESCP successfully in Malaysia by determining the common challenges for implementing ESCP and identify the factors for implementing ESCP successfully. The common challenges for implementing ESCP can be divided into two (2) which are internal challenges and external challenges. Furthermore, the successful factor implementing ESCP can be categorized into four factors: strategic focus, people, operations, and finances. This study will create awareness, knowledge, and importance of ESCP, improve the rate of success of implementation ESCP in Malaysia, and help in the decision making and tackle the problem related to the implementing of ESCP.